Focal vibrations enhance somatosensory facilitation in healthy subjects: A pilot study on Equistasi® and high-frequency oscillations - Cruciani, Alessandro; Lanzone, Jacopo; Musumeci, Gabriella; Di Lazzaro, Vincenzo; Marano, Massimo (Frontiers in Neurology, 2022)
Background: Equistasi® is a vibrotactile device composed of nanotechnology fibres able to convert temperature change into mechanical energy by self-producing a focal vibration. It is used in non-pharmacological rehabilitation in movement disorders patients and in multiple sclerosis sequelae. Nonetheless, the mechanism behind such an improvement of motor functions is still poorly understood Objectives: We designed a small uncontrolled pilot trial to explore the effect of Equistasi® on the somatosensory pathway investigated through the analysis of high-frequency oscillations (HFOs). Methods: For all the subjects we recorded somatosensory evoked potentials (SEP) at baseline (T0) and 60 minutes after the application of Equistasi® (T1) on the 7th cervical vertebra level and at the forearm over each flexor carpi radialis, bilaterally. Then, we extract the HFOs from the N20 signal and compare the HFOs duration and area under the curve pre and post Equistasi® application. Results: At a head-to-head comparison of T0 vs T1 data, there was a statistically significant reduction of the total HFO area (p<0.01), which was prominent for the late component (p = 0.025). No statistical differences have been found between T0 and T1 HFOs duration (p>0,05). We further evaluate the N20 amplitude from onset to N20 peak to avoid possible interpretational bias. No statistical differences have been found between T0 and T1 (p = 0,437). Conclusion: Our clinical hypothesis supported by preliminary data is that vibrotactile afference delivered by the devices could work by interfering with the somatosensory processing rather than by peripheral effects.